Strengthening high school teachers’ organizational commitment: The role of authentic leadership, school climate, and procedural justice - Suhaenah, Een; Sujanto, Bedjo; Matin, Matin (Edelweiss Applied Science and Technology, 2025)
This study aims to examine the influence of authentic leadership, school climate, and procedural justice on the organizational commitment of teachers at public senior high schools in Bekasi Regency. The research involved 321 teachers as respondents, using a quantitative approach with data collected through surveys. Data analysis was conducted using Structural Equation Modeling (SEM). The results indicate that authentic leadership has a significant direct effect on teachers’ organizational commitment, as do school climate and procedural justice. Furthermore, authentic leadership and school climate were also found to have a direct impact on procedural justice. Additional findings reveal that authentic leadership and school climate indirectly affect organizational commitment through the mediation of procedural justice. Overall, these findings underscore the importance of authentic leadership, a positive school climate, and the implementation of procedural justice in enhancing teachers’ organizational commitment, which in turn can contribute to improving the quality of education in Bekasi Regency.